Ship resistance and flow - Larsson, Lars; Raven, Hoyte C. (Principles of Naval Architecture series, 2010)
This volume contains a completely new presentation of the subject of ship resistance embodying these developments. A major goal in the design of virtually all vessels is to obtain a hull form having low resistance. In achieving this goal, the accurate prediction of resistance for a given hull geometry is essential. Since the publication of the previous edition of PNA important advances have been made in theoretical and computational fluid dynamics accompanied by increased use of such work in ship and offshore structure design.